PENGARUH MODEL PBL BERBANTUAN VIDEO TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI PECAHAN DI SEKOLAH DASAR - Bees, Yuningsi; I. Bien, Yusak; E. Lakapu, Dyen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking skills are essential in mathematics learning, particularly in fraction topics. However, elementary school students’ critical thinking skills remain relatively low because learning activities tend to be teacher-centered and provide limited opportunities for students to engage in problem-solving activities. This study aimed to determine the effect of the Problem-Based Learning (PBL) model assisted by instructional videos on students’ critical thinking skills in fraction learning among fourth-grade students at SD Inpres Kobelete. This study employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest design involving 24 students from Class IV A selected through purposive sampling. Data were collected through written tests in the form of contextual essay questions and observation sheets of learning activities. Data analysis was conducted using the Shapiro–Wilk normality test as a prerequisite test, the Paired Samples t-Test to test the hypothesis, and the N-Gain test to measure the level of improvement in students’ critical thinking skills with the assistance of SPSS software. The results showed that the average score of students’ critical thinking skills increased from 50.83 on the pretest to 74.17 on the posttest. Students’ critical thinking activities were categorized as good, with a percentage of 75.63%. The Paired Samples t-Test result showed a significance value (2-tailed) of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. The improvement in students’ critical thinking skills was classified as moderate, with an average N-Gain score of 0.47. Based on these findings, it can be concluded that the implementation of the Problem-Based Learning model assisted by instructional videos has a significant effect and is effective in improving students’ critical thinking skills in fraction learning among fourth-grade students at SD Inpres Kobelete.